Quantitative Study of Impurities in Bedaquiline Fumarate: Identification and Characterization of Its Three Degradation Products Using HPLC, LC/ESI-MS, and NMR Analyses - Xiao-Wen Zhang; Gang-Long Jiang; Guo-Jing Li; Xiao-Yan Chen; Ai-Nan Zhou; Yu Liu (Georg Thieme Verlag KG, 2023)
Abstract The study aimed to establish a high-performance liquid chromatography (HPLC) method for the quantitative analysis of the related substances of bedaquiline fumarate. Nuclear magnetic resonance and mass spectrometry were used for characterization and assay. A chromatographic method was used for separation. The conditions used were: gradient elution system composed of methanol 0.01mol/L KH2PO4 and 0.01 mol/L K2HPO4 (pH = 4.1) with a flow rate of 1 mL/min, at 224 nm as the detection wavelength. In this study, three degradation products of bedaquiline fumarate have been disclosed for the first time. The related impurities and degradation products of the drug were well separated. The method provided linear responses within the concentration range, which varied from 0.20 to 10.08 μg/mL with limits of detection of 0.10 μg/mL and limits of quantification of 0.20 μg/mL. The mean percent recovery varied between 91.64 and 105.89%. The method was validated for other parameters such as specificity, stability, and robustness. This method was validated and worked well for the impurity studies and quality control analysis of the laboratory-prepared samples of bedaquiline fumarate.